Attack of malicious objects in computer network under antivirus and quarantine defence - Singha, Anjani Kumar (IJRDO -Journal of Computer Science Engineering, 2017)
Here we develop an epidemic model in a computer network under quarantine and antivirus treatment.Effect of antivirus in the computer network prevents rapidly the spreading behaviour of maliciousobjects and the role of Quarantine treatment in a computer network increases recovery rate of theinfectious computers. The stability of the model and basicreproduction number ( R0V) of the model is also derived. Moreover, the effect of antivirus andquarantine in the systemis analyzed. MATLAB is employed to solve and simulate the dV       system of equations. S The( simulated)V resultsVI help us to dtunderstand the spread and control of malicious objects in acomputer networkdIdt. SI   VI (    ) I I